Toward a Christological Model of Leadership: Understanding Ethical and Moral Leadership Through a Sacred Texture Analysis of Philippians 2:5-11 - Jones-Carmack, Joy (Journal of Leadership, Accountability and Ethics, 2020)
Utilizing social rhetorical criticism and sacred texture analysis, this exegetical study examined the Christological model of leadership presented in Philippians 2:5-11. Although previous research has labeled Christ a servant leader, this analysis revealed that while servant leadership must be part of the Christian model, Christological leadership exceeds servant leadership. Comparing the Pauline model of leadership with the theory of cognitive dissonance and the theory of behavioral integrity illustrated that ethicality and morality are not issues of theory, but of praxis. Ultimately, the Kenosis Hymn provides contemporary leaders with an exemplar model of ethical leadership that emphasizes removing cognitive dissonance and implementing behavioral integrity